Early Savings Socialization in Sidadadi Village, Haurgeulis District, Indramayu Regency - Annita Widiastuti; Didik Himmawan (Konsultan Jurnal Ilmiah Indonesia, 2025)
The role of students is very important in changing various aspects of society. Therefore, students are expected not only to focus on learning in college, but also to be active in contributing to society. One way to carry out this contribution is through community service activities which are part of the implementation of the Tri Dharma of Higher Education. Sidadadi Village in Haurgeulis District, Indramayu Regency, was chosen as the location for PkM. We aim to provide education on financial management, how to manage finances from an early age for children in Sidadadi Village. Socialization is one of the means of the learning and teaching process. The purpose of socialization is to provide an understanding of something to individuals and community groups. Saving is important in terms of financial management. Saving is an activity of setting aside money for a certain period of time that can be used in the future. Knowledge about finance is not only intended for adults or parents, but early childhood needs to be given an understanding and good habits that can be useful in the future. Elementary School located in Sidadadi Village, Haurgeulis, Indramayu became the destination for community service activities where the participants of this activity were children of Sidadadi Village with an age range of 7 to 12 years. The main strategy in this activity is to provide knowledge about saving to early childhood children and in this learning activity we use intermediary media as a means to train children's knowledge and creativity. Providing knowledge about saving which also trains children's creativity is expected to be easier to understand by children in Sidadadi Village. The importance of introducing money and the concept of saving through the Education Activity on the Importance of Saving from an Early Age aims to explain and provide an understanding of achieving ideals, providing knowledge to participants about the introduction of money. The level of awareness, understanding and thinking of children regarding the importance of living frugally and saving should be known from an early age. This aims to prepare themselves and their understanding to be more disciplined in managing and managing finances and wise in using the amount of their savings in the future with various needs.